Electronic transport studies of highly-polarized compensated ferrimagnetic thin films: Mn2RuxGa - Jha, Ajay Kumar (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
Abstract Modern day information technologies not only rely on miniaturization and densification of data processing and data storage, but also on fast data transmitters and receivers. Current CMOS based technologies are limited to tens of GHz read and write speeds, at least for ambient temperature operation. Alternative approaches come from areas like spin electronics, using different principles and material sets. Here we build an approach relying on highly spin-polarized low-moment magnetic materials as the active building blocks in switching and oscillation devices. One particular material class, which has been predicted in 1995 by val Leuken: the zero moment half metals (ZMHM) could potentially offer solutions for achieving high-frequency operation magnetic devices, well into the THz region. Despite the early prediction, the potential of ZMHMs was not realized experimentally until 2014, with Mn2RuxGa (MRG) being the first known prototype. Narrow-band ferromagnetic resonance, well above 0.2 THz, where the central frequency is determined by the anisotropy field within the material, has already been demonstrated in the Mn-Ga family. Tantalizing prospects emerge, for the realization of spintronic oscillators and switchers, operating well into the THz region, by exploiting higher-order anisotropy effects and non-linear excitation, relying on either high galvanic current densities and spin-transfer or spin-orbit torques, or on optical excitation, using ultra-short laser pulses. Here we deploy a number of primarily electronic transport-based techniques to shed light over all essential effective parameters necessary for device design using MnGa-based materials, including junction transport in superconductor-ferrimagnet dynamically-formed contacts, anomalous Hall effect in lithographically defined bars at both low and high current densities. The basic spintronics theory is introduced first, before details are provided on the theoretical framework for the analysis of specialized measurement data, such as point contact Andreev reflection (within the modified Blonder-Tinkham-Klapwijk formalism) and spin-orbit torque, within the sub-lattice macrospin approximation. A separate chapter is dedicated to the description of the measurement techniques, methodologies and equipment used in this work, including examples from the literature, before going into discussing experimental and modelling efforts in three complementary directions: systematic investigation of the Fermi-level polarization as a function of the composition in the MRG-family of materials, an exhaustive determination of the effective low-frequency dynamics and quasi-statics torque parameters, and the changes in these in the high-current density transport regime. The investigation of the possibilities of Fermi level engineering of MRG films, primarily by tuning electronic pressure, (using the Mn/Ru ratio in the films), is presented first. It highlights the importance of electronic pressure (via a combination of substrate-induced strain and chemical pressure) in MRG for the achievement of very high Fermi level spin-polarization (>63 % has been observed). Here the quantification of spin-polarization is done by means of point contact Andreev reflection (PCAR) spectroscopy. A detailed analysis of the magnetocrystalline anisotropy of MRG samples by means of the anomalous or spontaneous Hall effect (AHE) follows. In MRG, the AHE is sensitive towards the out of plane component of the magnetization of primarily one of the two spin sub-lattices, which contributes most of the DOS at the Fermi level. It also allows for the determination of the torque acting on the same. This is rather useful in thin epitaxial films, of low-moment materials, where the conventional bulk techniques (such as SQUID magnetometry) run out of sensitivity. A new methodology is proposed for the comprehensive determination of the anisotropy constants in thin film with substantial AHE, which relies on obtaining data for different field rotations, conducted at varying field strengths. In MRG, the out of plane anisotropy constants are determined as follows: K_1=4?10^4 J m^(-3) (K_1?M=0.655 T), K_2=2.54?10^4 J m^(-3) (K_2?M=0.416 T) and in-plane effective anisotropy constant is evaluated as K_3=3.48?10^3 J m^(-3) (K_1?M=0.057 T), all by fitting the anomalous Hall resistance to a consistent set of torque models, under the macrospin approximation. First order reversal curves (FORCs) and a classical Preisach hysteresis (hysterons) model are deployed in the modelling of the hysteretic response of the structures and assert the validity of the macrospin approximation and help to determine effective magnetic viscosity parameters. The measurements of current induced spin orbit torques in single-layer MRG films are presented and discussed last. The effective spin-orbit field is high, without the need to involve any heavy metal over-layers, with values in excess of 5?10^(-12) TA^(-1) m^2 at low current density and 75?10^(-12) TA^(-1) m^2 at a current density of only j=2.5?10^10 Am^2. The high values of the observed intrinsic spin-orbit torques in MRG suggest alternative approaches to the realization of spintronic oscillators for the upper GHz and the THz bands, relying on high current densities conducted in-plane, within essentially all-metal micronic-size structures, rather than perpendicular-to-plane through critical tunnel barriers, within nano-pillars. In the conclusions of this thesis we argue that highly-polarized compensated ferrimagnets may indeed hold the right combination of high effective torques, low precession moments, low damping and high resonance frequencies to put spin electronics back into the beyond CMOS race.
APPROVED
Keywords: Heusler alloys; Compensated ferrimagnetic half-metal; Magnetic thin-films; Spin-polarization; Point-contact Andreev reflection (PCAR) spectroscopy; Anomalous Hall effect; Magnetic anisotropy; Preisach model; Hysteron model; First order reversal curve (FORC) method; Torque model; Non-linear quasi-static spin dynamics; Spin-orbit torque; Spin oscillator